Analisis Faktor-Faktor yang Mempengaruhi Pengungkapan Islamic Social Reporting Pada Perusahaan yang Terdaftar di Jakarta Islamic Index Periode 2019 – 2021 - Fauziah, Putri Roifatul; Afifudin, Afifudin; Anwar, Siti Aminah (Universitas Islam Malang, 2023)
This study aims to explain the factors that influence the disclosure of Islamic social reporting in companies listed on the Jakarta Islamic Index. The independent variable indicators of this research are profitability, company size, company age, and leverage. The dependent variable indicator of this research is Islamic Social Reporting (ISR). The data used is secondary data, obtained from the Unisma Faculty of Economics and Business Investment Gallery and the official website www.idx.co.id. Sampling was carried out using purposive sampling method. The sample for this research is 22 companies registered in the Jakarta Islamic Index for the 2019-2021 period. Data analysis used the classical assumption test and multiple linear regression. The results of this study indicate that simultaneously Profitability, Firm Age, Firm Size and Leverage have a significant effect on Islamic Social Reporting. partially shows that Profitability has no effect on Islamic Social Reporting. partially shows that Firm Age, Firm Size and Leverage have a significant effect on Islamic Social ReportingKeywords: Profitability, Company Size, Company Age, Leverage, Islamic Social Reporting